Adolescent indirect reciprocity: Evidence from incentivized economic paradigms. (26th June 2019) - Hu, Yang; Ma, Jichang; Luan, Ziyan; Dubas, Judith Semon; Xi, Juzhe
ABSTRACT: Introduction: Indirect reciprocity serves as a crucial component of how we interact with strangers. Two types of indirect reciprocity can be distinguished: pay‐it‐forward reciprocity and third party reciprocity. Pay‐it‐forward reciprocity refers to behaviors where people who have been treated well by others (either fairly or generously), extend that fairness or generosity to a stranger. Third‐party reciprocity refers to behaviors where third‐party bystanders altruistically punish those who transgress against others or kindly help the victims. The expansion of adolescents' social world increases opportunities to exercise indirect reciprocity yet very little research has focused on this topic in this age group. The current research addresses this lacuna and investigates how younger adolescents differ from older adolescents in pay‐it‐forward and third party reciprocity. Methods: With incentivized economic paradigms, we investigated both types of indirect reciprocity in younger ( n  = 50) and older adolescents ( n  = 46). Results: The pay‐it‐forward task revealed that receiving an equal (vs. unequal) distribution led both younger and older adolescents to become fairer to a third person. In the third‐party task, older adolescents were more likely to devote their own resources to enforce fairness norms than younger adolescents. Conclusion: Our results shed light on how adolescents perceive and act in complex social settings where direct reciprocity is unrealistic. Both younger and older adolescents are capable of engaging in both forms of indirect reciprocity with older adolescents being more discriminative in their norm‐enforcing behaviors.